2019
DOI: 10.1142/s1464333219500182
|View full text |Cite
|
Sign up to set email alerts
|

SEA, Urban Plans and Solid Waste Management in Kenya: Participation and Learning for Sustainable Cities

Abstract: This paper examines the role of participation and learning in Kenyan strategic environmental assessments (SEAs) of urban plans that include a solid waste management (SWM) component. Two SEA cases were studied using 40 semi-structured interviews and two focus groups. Data are analysed qualitatively employing NVivo software. Participation is assessed using ideal conditions of learning derived from Transformative Learning Theory, and operationalised for this study. Strengths of SEA participation are freedom from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The role of tourism development as a factor in energy consumption and stimulating energy consumption patterns has hitherto not been considered as a major factor in the literature. The different channels of tourism development influence economic development, resources, energy use patterns, and carbon emissions, and therefore, the empirical framework (Khosravi et al 2019;Kordej-De Villa and Slijepcevic 2019;Ozoike-Dennis et al 2019;Sovacool et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The role of tourism development as a factor in energy consumption and stimulating energy consumption patterns has hitherto not been considered as a major factor in the literature. The different channels of tourism development influence economic development, resources, energy use patterns, and carbon emissions, and therefore, the empirical framework (Khosravi et al 2019;Kordej-De Villa and Slijepcevic 2019;Ozoike-Dennis et al 2019;Sovacool et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The National Solid Waste Management Strategy is used to incorporate solid waste management and best practices into urban plans. The plans are then subjected to a Strategic Environmental Assessment, which assesses aspects such as sustainability, proposed waste management programs, as well as relevant services and facilities (Ozoike-Dennis et al 2019). The authors further state that solid waste management (SWM) plans are included in the Nairobi Integrated Urban Development Master Plan (NIUPLAN).…”
Section: Evolution Of Sustainable Urban Planning In African Citiesmentioning
confidence: 99%
“…Governance determines public management of cities, which affects the use of natural resources and the functioning of the market forces, both of which in turn affect society (El-Kholei, 2019). In the majority of cases, it was indicated that governance -or strong collaborations between governments and other actors in managing resources -play a strategic role to ensure that sustainable cities may be achieved in the long term (Ozoike-Dennis et al, 2019;Staukis, 2014).…”
Section: State Of the Artmentioning
confidence: 99%